Research of Roof Anchorage Rock Beam Bearing Structure Model of Extra-Large Width Open-Off Cut and Its Engineering Application in a Coal Mine, China - Shengrong Xie; Qing Zhang; Dongdong Chen; En Wang; Junchao Zeng; Chunwei Ji; Xiaoyu Wu; Zaisheng Jiang; Feng Chen; Shunxing Qiao (Advances in Civil Engineering)
The stability of the extra-large width open-off cut of a longwall panel has been a major concern in underground solid backfill mining. In this study, a numerical model was built with FLAC3D for analyzing the characteristics of the effective prestressed field distribution in the extra-large width open-off cut roof in Xingdong coal mine, China. The numerical results obtained in this study demonstrate that an anchorage rock beam bearing structure (ARBBS) can be formed. Additionally, the ARBBS model was also constructed. The analytical expression of the maximum shear stress (MSS) in the model was obtained under the functions of composite influencing factors. Then, the MSS evolution laws in ARBBS with different thicknesses and spans were investigated using MATLAB software. The stress changes in ARBBS with a span of 15 m were compared and analyzed under the functions of single and composite influencing factors. The cooperative control principle of the roof ARBBS and two rib anchorage bearing structures was also clarified. Accordingly, a combined support scheme for an 11.5 m-wide open-off cut was proposed. The field applications demonstrated that the scheme successfully controlled the failure and deformation of the surrounding rock, thus contributing to the fast development of the open-off cut and the quick and timely installations of the backfill mining equipment. This validated the results of the ARBBS model. This study is expected to provide helpful references for other extra-large width open-off cut or roadway stability investigations and rock support design under similar engineering and geological conditions.